2010
DOI: 10.1038/hr.2009.222
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytokines and endothelial function in preeclamptic women

Abstract: Visceral fat accumulation stimulates the production of adipocytokines in patients with metabolic syndrome. Excess body weight gain during pregnancy is a risk factor for preeclampsia. To evaluate whether the pathogenesis of preeclampsia is similar to that of metabolic syndrome, we measured plasma adipocytokine concentrations and investigated the association between plasma adiponectin concentrations and body weight gain or endothelial function in preeclamptic women. We investigated 15 preeclamptic and 17 women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 31 publications
(31 reference statements)
2
37
0
Order By: Relevance
“…Five studies reported on insulin levels 37, 45, 55, 62, 75. Three met the requirements for a meta‐analysis,37, 55, 75 revealing higher insulin levels in pre‐eclampsia than in controls with mean difference 1.31 μU/mL; 95%CI 0.93–1.70; P  < 0.00001.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Five studies reported on insulin levels 37, 45, 55, 62, 75. Three met the requirements for a meta‐analysis,37, 55, 75 revealing higher insulin levels in pre‐eclampsia than in controls with mean difference 1.31 μU/mL; 95%CI 0.93–1.70; P  < 0.00001.…”
Section: Resultsmentioning
confidence: 96%
“…Thirty‐two studies in total reported on C‐reactive protein levels,21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52 of which 17 were applicable for meta‐analysis 21, 22, 23, 29, 30, 31, 32, 33, 34, 37, 38, 39, 41, 42, 47, 49, 50. A significantly higher C‐reactive protein was found in women with pre‐eclampsia than in non‐hypertensive controls ( Figure 2), and this correlation was stronger in severe than in mild pre‐eclampsia ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, flow-mediated vasodilation (FMD) of the brachial artery, a known marker of vascular endothelial function, was decreased in preeclamptic women. 4) There is also a negative correlation between FMD and levels of derivatives of reactive oxygen metabolites (d-ROMs) in all pregnant women. These results support the notion that in preeclamptic women, endothelial damage is associated with oxidative stress, which is caused by increased oxygen free radical production.…”
Section: Introductionmentioning
confidence: 99%